UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI TATA SURYA MELALUI MODEL PEMBELAJARAN QUANTUM TEACHING DI KELAS VI SDN 067259 KEC MEDAN JOHOR: Penelitian Tindakan Kelas - Suci Rahmadani Siregar; Rumiris Lumban Gaol (STKIP Subang, 2025)
This study is a Classroom Action Research (CAR) aimed at improving student learning outcomes on the topic of the solar system through the implementation of the Quantum Teaching learning model in Grade VI at SDN 067259, Medan Johor District. The background of this research is the low student learning outcomes on the solar system material, caused by the lack of variety in teaching methods and limited student engagement during the learning process. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 30 sixth-grade students. Data collection techniques included tests, observations, interviews, and documentation. The results showed an increase in student learning outcomes from Cycle I to Cycle II. In Cycle I, the percentage of students who achieved mastery learning was 66.67%, which increased to 86.67% in Cycle II. In addition, student engagement in the learning process also improved. Thus, the implementation of the Quantum Teaching model proved effective in enhancing student learning outcomes on the topic of the solar system.